The Intention Gap Between Environmental Attitudes and Green Purchase Behavior in Personal Care Product Purchases by Women with Children - Putri, Dinanti Amelia; Santoso, Indriyani; Akbar, Amin; Ayu, Rindang (LPPM Universitas Jambi, 2026)
A rise in environmental challenges owing to society consumption patterns highlights the importance of Green Purchase Behavior, especially in the context of buying personal care products. Environmental Attitude is a suggested factor influencing the tendency toward Green Purchase Behavior since women with children play significant roles in family purchasing. However, research on the relationship between Environmental Attitude and Green Purchase Behavior shows varied findings and inconsistent. This study aims to examine the effect of Environmental Attitude on Green Purchase Behavior among women with children when purchasing personal care products. A quantitative approach was used, employing scales for Environmental Attitude adapted from Dunlap., et al (2000) and Green Purchase Behavior Scale adapted from Lee (2007). The study sample consisted of 135 women with children who are aware of eco-friendly personal care products. Analysis results show that Environmental Attitude significantly influences Green Purchase Behavior, accounting for 9.3% of the effect, while the remaining influence comes from other factors not studied here. This indicates that higher Environmental Attitude levels correspond to a greater tendency toward Green Purchase Behavior. However, the independent variable's influence is relatively low, implying that other factors also affect Green Purchase Behavior. The findings are expected to shed light on the role of environmental attitudes in shaping green purchasing behavior, as well as serve as a foundation for developing social and educational initiatives that encourage pro-environmental purchasing practices among communities while guiding industries in supporting environmentally responsible consumer behavior.